Children and the Internet: Learning, in the Times to Come - Sugata Mitra (Commonwealth of Learning, 2020)
It is proposed that the purpose of education is to enable people to live happy, healthy and useful lives — now and in the future. A curriculum and framework for children’s education is derived from the above purpose. Using the results of over twenty years of research, the pedagogical and physical environments required that will enable children to learn are discussed in the post-pandemic world. Scenarios for schools and homes are presented with a special emphasis on the role of the Internet in children’s learning. New methods for assessment and certification are described to complete a framework for children’s education that is fit for purpose for our times.